Contraceptive trend in a tertiary facility in North Western Nigeria: A 10‑year review - Muhammad, Z.; Maimuna, D. G. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Of all the direct influences on fertility, contraceptive use is the single most important factor for reproductive health policy makers and program managers. Increase in its use accounted for the largest proportion of fertility decline worldwide including the sub-Saharan region.Objective: To determine the trends of contraceptive use and the preferred method of contraception among the clients visiting the family planning clinic of Aminu Kano Teaching Hospital, Kano.Study Design: This is a retrospective descriptive study, involving all acceptors of contraceptive methods from January 1999 and December 2008 in the family planning unit of Aminu Kano Teaching Hospital Kano, Nigeria.Results: A total of 35,792 clients booked for antenatal care at Aminu Kano Teaching Hospital over the study period. Acceptors of contraceptive methods were 11,346 clients, giving contraceptive prevalence of 31.6%. The acceptors of modern contraceptive methods increased steadily from a total of 1009 in the year 1999/2000 to 3014 the year 2007/2008. Approximately 65% of the clients used the Injectables; implant was the least used, by 2% of the clients. Female sterilization contributed about 3.4%, intrauterine contraceptive device (CUT 380A) 16.6%, male condom 2.8%, and oral contraceptive pills 10.4%. There was a significant increase in the trend of use of modern hormonal contraceptive methods as compared to the non hormonal methods. χ2trend= 87.21,P= 0.00000. No man had vasectomy over the 10-year period.Conclusion: There is an increase in the trend of contraceptive use over the study period. Injectable contraceptives are the most commonly used method in this study.
Keywords: Aminu Kano teaching hospital; contraceptive; Kano; Nigeria; trends